Một số vấn đề cơ bản trong việc thiết kế bộ điều khiển trên cơ sở hệ luật - Cát, Phạm Thượng; Dũng, Lê Bá (Journal of Computer Science and Cybernetics, 2016)
Two kinds of the Rule-based Controller: Direct and Indirect Control are presented in this paper. The Rule-based Controllers use heuristic procedures based on Knowledges of experienced Control  Engineers and skilful plant operators. The Algorithm of Direct Control uses Fuzzy Logic Inferenced method and the Algorithm of Indirect Control has some levels using Expert method on high level.